2016
DOI: 10.1002/ejoc.201600567
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Observations on the Intramolecular Nucleophilic Addition of α‐Amino Carbanions to Arynes: Synthesis of 1‐Aryl‐1,2,3,4‐tetrahydroisoquinolines

Abstract: 1‐Aryl‐1,2,3,4‐tetrahydroisoquinolines (THIQ) are key intermediates and products in the pharmaceutical industry. A new method involving intramolecular nucleophilic addition of α‐amino carbanions to in‐situ‐generated arynes in N‐Boc‐protected (Boc = tert‐butoxycarbonyl) amine substrates is presented for the synthesis of these compounds. Surprisingly, a similar reaction in Lewis‐acid‐complexed tertiary amines failed. These results have been analysed using quantum chemical calculations on the intermediates involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 144 publications
0
5
0
Order By: Relevance
“…However, regioselectivity of lithiation in cyclic tertiary amines can be altered by prior treatment of amine with Lewis acid i. e. BF 3 or BH 3 [16a] . Our research group has established a novel synthetic approach for arylation which involved a coupling reaction of amino carbanion with in situ generated benzyne to give α/β‐arylated cyclic amines [15a,c,d,e] …”
Section: Resultsmentioning
confidence: 99%
“…However, regioselectivity of lithiation in cyclic tertiary amines can be altered by prior treatment of amine with Lewis acid i. e. BF 3 or BH 3 [16a] . Our research group has established a novel synthetic approach for arylation which involved a coupling reaction of amino carbanion with in situ generated benzyne to give α/β‐arylated cyclic amines [15a,c,d,e] …”
Section: Resultsmentioning
confidence: 99%
“…After the work up, the crude material was heated under reflux in 2 M HCl‐ethanol solution to remove the phosphinoyl group . The resulting oily mass obtained after usual work‐up was purified by column chromatography on silica gel to give 1‐aryl‐1,2,3,4‐tetrahydroisoquinoline in 51 % yield. The reaction conditions were optimized by varying the amount of base and amount of aryl halide.…”
Section: Resultsmentioning
confidence: 99%
“…Further more, we reported an intramolecular version of the above procedure which involved nucleophilic addition of α‐amino carbanions generated from N ‐Boc protected secondary amines to in situ generated benzynes for the synthesis of 1‐aryl‐1,2,3,4‐tetrahydroisoquinolines (Scheme ) . It is worth pointing out here that a similar attempt to generate α‐amino carbanion 6 from the Lewis acid complexed tertiary amines 5 failed to furnish the corresponding cyclized product 7 (Scheme ) . Reaction of 5 with s BuLi resulted in formation of β‐amino carbanion 5.Li which upon eliminationresulted in formation of N ‐methyl benzyl amine 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the lithiation technique has been applied in intramolecular nucleophilic addition of α-amino carbanion for the synthesis of 1-aryl-1,2,3,4-tetrahydroisoquinolines (Scheme 30). 45 Notably, Lewis-acid-complexed tertiary amines were unable to afford the same reaction under standard conditions. Computational studies confirmed that N-Boc group helped in generation of more stable anionic intermediate species as compared to N-BF3 complex.…”
Section: Intramolecular Arylationmentioning
confidence: 99%
“…Recently, the lithiation technique has been applied for the intramolecular nucleophilic addition of -amino carbanions for the synthesis of 1-aryl-1,2,3,4-tetrahydroisoquinolines (Scheme 30). 45 Notably, Lewis acid complexed tertiary amines were unable to undergo the same reaction under the standardized conditions.…”
Section: Intramolecular Arylationmentioning
confidence: 99%